Data for: Wolves make roadways safer, generating large economic returns to predator conservation - Raynor, Jennifer; Grainger, Corbett; Parker, Dominic (Zenodo, 2022)
This dataset includes information on deer-vehicle collisions, vehicle miles traveled, weather, and deer, wolf, and human populations, for counties in Wisconsin from 1981-2016. These details needed for data useage are described in the README.txt file. Funding provided by: National Institute of Food and Agriculture Crossref Funder Registry ID: http://dx.doi.org/10.13039/100005825 Award Number: Hatch Project No. 1006896